(untitled) (Al-Academy, 2021)
The Interior design is concerned with designing and creating internal spaces and reformulating their ideas, thus separating their capacities for influence and achieving suitability and comfort for their occupants, and enabling them to use them in a manner that achieves their goals and requirements, and this is unfolded by the integrity of the functional, aesthetic and expressive performance that these spaces achieve, The behavior of its users includes a variety of activities in harmony with the influence of those spaces and their forms, so the designer was keen to have these spaces in a form with an effective role in harmony with the needs of the times and its complexities in formation and construction, familiar with the strong cultural, scientific and technological influences that have achieved over time a revolution and a radical transformation of interior design and The intellectual changes accompanied and kept them away from the true meaning of the idea of traditional design by affirming conviction in the principle of trespass and not to be submissive to traditional rulings and their repetitions, which no longer represent the image of human progress and development at all levels.